2006
DOI: 10.1007/s10812-006-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and spectra of NH-isomers of isobacteriochlorin

Abstract: ev UDC 539.19Using the restricted and unrestricted Hartree-Fock method (RHF and UHF) with the AM1 Hamiltonian, we have calculated the geometric structure of the NH-isomers of isobacteriochlorin and its meso-cyano derivative. We have used the CNDO/S method for all the considered structures to calculate the transitions to excited electronic states. We have analyzed the effect of taking into account electron correlation on the results of the calculations of the chemical and geometric structure and the electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
5
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…These maxima are situated at 516 and 569 nm for H 2 TAiBC tt . Based on the calculations given below and the literature [17] and by analogy with other tetrapyrroles, it can be confirmed that these maxima do not belong to two separate electronic transitions. There are two possibilities.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…These maxima are situated at 516 and 569 nm for H 2 TAiBC tt . Based on the calculations given below and the literature [17] and by analogy with other tetrapyrroles, it can be confirmed that these maxima do not belong to two separate electronic transitions. There are two possibilities.…”
supporting
confidence: 52%
“…Luminescence of octaethyl H 2 iBC and its metal complexes have been studied [6,7], with most attention paid to polarized fluorescence spectra of the metal complexes [7] (the free base does not phosphoresce). Derivatives of H 2 iBC that are stabilized by adding two methyls to each of the β-carbons for both hydrogenated pyrrole rings, H 2 -2,2,7,7,12,13,17,18-octamethyl-iBC (H 2 OMiBC), and the analogous compound with a cyano group in the meso-position, H 2 -5-cyano-2,2, 8,8,12,13,17, COMiBC), have been synthesized [8,9]. The spectroscopic properties of these compounds were characterized [10][11][12][13][14][15][16], in particular, NH-isomerism in these types of molecules was observed.…”
mentioning
confidence: 99%
See 3 more Smart Citations